Clinal variation in a brown lemur (Eulemur spp.) hybrid zone: Combining morphological, genetic and climatic data to examine stability. (19th July 2013) - Delmore, K. E.; Brenneman, R. A.; Lei, R.; Bailey, C. A.; Brelsford, A.; Louis, E. E.; Johnson, S. E.
Abstract: Studies of hybrid zones can inform our understanding of reproductive isolation and speciation. Two species of brown lemur ( Eulemur rufifrons and E. cinereiceps ) form an apparently stable hybrid zone in the Andringitra region of south‐eastern Madagascar. The aim of this study was to identify factors that contribute to this stability. We sampled animals at 11 sites along a 90‐km transect through the hybrid zone and examined variation in 26 microsatellites, the D‐loop region of mitochondrial DNA, six pelage and nine morphological traits; we also included samples collected in more distant allopatric sites. Clines in these traits were noncoincident, and there was no increase in either inbreeding coefficients or linkage disequilibrium at the centre of the zone. These results could suggest that the hybrid zone is maintained by weak selection against hybrids, conforming to either the tension zone or geographical selection‐gradient model. However, a closer examination of clines in pelage and microsatellites indicates that these clines are not sigmoid or stepped in shape but instead plateau at their centre. Sites within the hybrid zone also occur in a distinct habitat, characterized by greater seasonality in precipitation and lower seasonality in temperature. Together, these findings suggest that the hybrid zone may follow the bounded superiority model, with exogenous selection favouring hybrids within the transitional zone. These findings are noteworthy, as examples supporting the bounded superiority model are rare and may indicate a process of ecologically driven speciation without geographical isolation.